2022
DOI: 10.1007/s11864-022-00955-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Supporting Informal Cancer Caregivers

Abstract: Opinion statement Informal caregivers invest a significant amount of time and effort to provide cancer patients with physical, psychological, information, and social support. These challenging tasks can harm their own health and well-being, while a series of social-ecological factors may also influence the outcomes of cancer caregiving. Several instruments have been developed to help clinicians and researchers understand the multi-dimensional needs and concerns of caregivers. A growing body of evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 130 publications
(166 reference statements)
0
25
0
Order By: Relevance
“…Especially in CGs of advanced cancer patients receiving palliative care needed long hours of caregiving, which had a greater impact on their incomes and further deteriorated their economic status. Molassiotis, A. et al found that low-income levels affected the caregiving process adversely and that CGs with highincome levels had a significant and positive effect on life satisfaction [5].…”
Section: Association Of Qol With Socio-demographic Variables Of Cgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in CGs of advanced cancer patients receiving palliative care needed long hours of caregiving, which had a greater impact on their incomes and further deteriorated their economic status. Molassiotis, A. et al found that low-income levels affected the caregiving process adversely and that CGs with highincome levels had a significant and positive effect on life satisfaction [5].…”
Section: Association Of Qol With Socio-demographic Variables Of Cgsmentioning
confidence: 99%
“…Diagnosis of cancer in the family impairs family function, which was significantly associated with depression and anxiety in both patients and caregivers. Increased demand for care and support from CG during treatment of terminal stage of illness, palliative care increases the vulnerability to psychological problems like anxiety, depression, and post-traumatic stress disorder in CG compared to cancer patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A global level systematic review and meta‐analysis reported a pooled prevalence of 42.3% depression and 46.55% anxiety among caregivers of Cancer patients 20 . Surprisingly, this high burden of mental health problems among caregivers didn't get attention and is subsequently not yet addressed clinically 21 …”
Section: Introductionmentioning
confidence: 99%
“…sequently not yet addressed clinically. 21 Caregivers' mental health can be enhanced by providing routine psychosocial support. [22][23][24] Further, health policymakers should develop evidence-based interventions capable of improving caregivers' physical and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation